Make your people before you make your products : using talent management to achieve competitive advantage in global organizations - Turner, Paul, 1952 October 18- (Wiley, 2014)
Written specifically for HR professionals, this book describes how organizations can gain a global competitive edge through better management of talent resources. With a practice-based philosophy, readers will learn more effective talent management strategies for a complex market in which people are often the only competitive advantage. Inclusivity is emphasized, and discussion centres on innovative, dynamic, fluid approaches to talent acquisition, development, and retention. This book provides practical guidance on more modern approaches, helping organizations to: attract and retain the best talent by expanding talent resource management; augment traditional management methods with more dynamic techniques; develop a talent strategy that recognizes the new diversity of supply and demand; consider the evolving roles of talent and leadership in a global context. --